Electrocautery damage can reduce implant fatigue strength: cases and in vitro investigation - Sonntag, Robert; Gibmeier, Jens; Pulvermacher, Samuel; Müller, Ulrike; Eckert, Johannes A.; Braun, Steffen; Reichkendler, Markus; Kretzer, Jan Philippe (The journal of bone & joint surgery. A, American volume, 2019)
Background: The risk of femoral stem fracture after total hip replacement is low and can often be associated with a specific implant system or other factors that may reduce the fatigue strength. Additionally, damage to a metal component during revision surgery by an electrocautery device may further affect the fatigue behavior. - Methods: Two clinical cases of stem failure after revision of fractured ceramic components are presented; the retrieved components were analyzed for the cause of failure. In vitro cyclic load-to-failure testing of titanium alloy femoral stems after electrocautery application at 2 different locations (at the base and about midway on the femoral neck) was performed using a stepwise increase in load until implant fracture occurred. In addition, a detailed characterization of the local material structure around the electrocautery marks was performed. Results: Superficial discoloration and melting marks were found on the retrieved components, including at the location of crack initiation in the anterolateral region, which may have reduced the fatigue strength of the material. In addition, elemental analysis indicated material transfer from the electrocautery tip. Damage to the surface by the electrocautery device significantly reduced the in vitro load to failure by up to 47% compared with that of undamaged femoral neck specimens. Material analysis revealed a relevant modification in microstructure, with an extension of approximately 2.7 mm and a depth of 550 µm, which could be divided in 3 structural zones. Conclusions: Intraoperative electrocautery device contact with the implant during surgical revision of a total hip replacement cannot always be avoided. However, on the basis of our findings, the risk of implant failure is increased due to a change in microstructure and a potential reduction of the implant’s fatigue strength. Surgeons and manufacturers of electrocautery devices should be aware of this concern. Clinical Relevance: During revision surgery, contact between an electrocautery device and the femoral component should be avoided to reduce the chance of subsequent femoral neck fracture.